2014
DOI: 10.1080/13571516.2013.835970
|View full text |Cite
|
Sign up to set email alerts
|

The Size Distribution of US Banks and Credit Unions

Abstract: This study examines the firm size distribution of US banks and credit unions. A truncated lognormal distribution describes the size distribution, measured using assets data, of a large population of small, community-based commercial banks. The size distribution of a smaller but increasingly dominant cohort of large banks, which operate a high-volume low-cost retail banking model, exhibits power-law behaviour. There is a progressive increase in skewness over time, and Zipf's Law is rejected as a descriptor of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Our results compare well with some of the existing studies of interbank networks, but differ from others. Specifically, our findings are in line with Goddard et al [8] who study U.S. banks: the log-normal distribution fits the bulk part of the asset-size data well, while the power law does the same for the tail part. Our findings are not too different from those of Cont et al [4] for the Brazilian interbank network: while our TPL fits to the tails of various degree distributions (see Table III) deliver values of α between 1.7 and 2.2, Cont et al [4] report power-law exponents between 2.2 and 2.8 (α = 2.54 for total degree, α = 2.46 for in-degree, α = 2.83 for out-degree, and α = 2.27 for out-exposure size).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our results compare well with some of the existing studies of interbank networks, but differ from others. Specifically, our findings are in line with Goddard et al [8] who study U.S. banks: the log-normal distribution fits the bulk part of the asset-size data well, while the power law does the same for the tail part. Our findings are not too different from those of Cont et al [4] for the Brazilian interbank network: while our TPL fits to the tails of various degree distributions (see Table III) deliver values of α between 1.7 and 2.2, Cont et al [4] report power-law exponents between 2.2 and 2.8 (α = 2.54 for total degree, α = 2.46 for in-degree, α = 2.83 for out-degree, and α = 2.27 for out-exposure size).…”
Section: Resultssupporting
confidence: 92%
“…In addition, many authors propose a power law as the best-fit candidate to (at least the tail of) the empirical distribution. In particular, Goddard et al [8] find that the asset size distribution of U.S. commercial banks is well described by a truncated lognormal, while the tail part is well fitted with a power law. Cont et al [4] obtain fair fits to the tails of the in-degree, out-degree, total degree, and exposure size distributions of the Brazilian interbank network with power laws.…”
Section: A Data Sourcementioning
confidence: 99%
“…In this case, the lognormal distribution overestimates the size of the large firms. On the other hand, Goddard et al [15] examine firm size among banks and credit unions based on Zipf's law. Their study rejects Zipf's law as a descriptor of the firm size distribution in the upper tail.…”
Section: Introductionmentioning
confidence: 99%
“…A strand of the empirical literature has thus sought to examine the application of lognormal and Pareto or power-law distributions using firm size data as cross-sectional data [13] [14] [15]. However, there is evidence that, on some occasions, a poor approximation of the empirical distributions of the firm size in the upper tail, which typically exhibit greater asymmetry as a small number of large firms exist alongside a large number of smaller firms [1] [12] [16], is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have found evidence that the lognormal distribution accurately fits to FS, favoring Gibrat's law [13][14][15], other studies feature a poor performance of this distribution, especially in the higher quantiles [16][17][18][19]. In this line, some empirical studies have shown that FS distribution can be adjusted using a Pareto or Power-law distribution [7,[20][21][22], although this latter distribution presents the shortcoming of requiring the selection of a minimum threshold to assume that FS distribution is well defined [3,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%